The importance of scientific method for psychological science - Haig, Brian D. (Psychology, crime & law, 2019)
This article is concerned with the nature of scientific method and its importance for psychology. It begins by considering the nature of scientific methodology as an essential source for a proper understanding scientific method. This is followed by an outline, and short assessment, of three major theories of the scientific method: hypothetico-deductive method, inductive method, and inference to the best explanation. Thereafter, a broad abductive theory of scientific method, that has particular relevance for psychology, is presented. Finally, the value of the scientific method for a genuine education in science is considered.